2016
DOI: 10.1108/jkm-04-2016-0177
|View full text |Cite
|
Sign up to set email alerts
|

The impact of focus, function, and features of shared knowledge on re-use in emergency management social media

Abstract: Purpose The purpose of this study is to investigate how organizations use social media such as blogs to share and re-used knowledge during contingencies, disasters, and emergencies. The factors related to the knowledge itself – rather than the media – which lead to more and less re-use (particularly in the fast-paced and uncertain context of emergencies) are not well known. Design/methodology/approach Integrating theories of social media, knowledge management and mass communication, the author develops a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Emergence of social media tools in recent times has given new opportunities to researchers to examine these aspects of KS. The early adoption of these tools for KS (Grant, 2016), specifically sharing of tacit knowledge (Panahi et al, 2013), and their use for exploiting knowledge during emergencies, contingencies and disasters (Yates, 2016) have been examined. Five emerging themes in social media research in context of KS were identified as "socialising, practising, networking, storytelling and encountering" (Panahi et al, 2013, p. 379).…”
Section: Resultsmentioning
confidence: 99%
“…Emergence of social media tools in recent times has given new opportunities to researchers to examine these aspects of KS. The early adoption of these tools for KS (Grant, 2016), specifically sharing of tacit knowledge (Panahi et al, 2013), and their use for exploiting knowledge during emergencies, contingencies and disasters (Yates, 2016) have been examined. Five emerging themes in social media research in context of KS were identified as "socialising, practising, networking, storytelling and encountering" (Panahi et al, 2013, p. 379).…”
Section: Resultsmentioning
confidence: 99%
“…In particular, it describes the five different types of justification at play and further enriches the understanding of collective sensemaking during a rumor. Extending previous research on the use of social media for KM purposes during crises (Yates, 2016), the current work suggests a more granular treatment of the notion of justification on social media to inform KM practices. For example, attention ought to be paid to descriptive argumentation during the early stage of the crisis, and evidentialism during the later stage.…”
Section: Discussionmentioning
confidence: 70%
“…This paper embraces the social constructivism view of knowledge, which is particularly apt in situations of ambiguity such as rumor outbreaks (Yates, 2016). The social construction of knowledge inevitably entails justification which not only shapes how individuals make sense of a given situation but also allows them to rationalize their decision-making (de Kwaadsteniet et al, 2007;Oh et al, 2013).…”
Section: Knowledge and Justificationmentioning
confidence: 99%
“…This result is supported in several studies that recognize BGs as useful tools, not only for the exchange of knowledge within firms (Baxter and Connolly, 2014) but also between different organizations. In this sense, Yates (2016) notes that BGs have allowed organizations to be lightly connected, allowing them to find the knowledge needed to implement them quickly in their decisionmaking. Therefore, this application has the potential to improve firms' competitiveness.…”
Section: Discussion Of Awsmentioning
confidence: 99%